2020
DOI: 10.1186/s12903-020-01113-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of self-assessed chewing ability, tooth loss and serum albumin on mortality in 80-year-old individuals: a 20-year follow-up study

Abstract: Background: The association between dental status and mortality in community-dwelling older adults has been documented by several studies. The aim of this study was to analyze the contribution of self-assessed chewing ability, number of remaining teeth and serum albumin levels to mortality and the interactions between the three factors. Methods: A 20-year follow-up study was conducted with 666 subjects aged 80 years (from 1996 to 2017) who resided in the 8 areas served by one health center in Iwate Prefecture.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 53 publications
1
39
0
Order By: Relevance
“…Several studies have shown that oral functions and number of remaining teeth have statistically significant correlation with the mortality of older adults [ 10 ]. However, the number of remaining teeth was conflicting.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have shown that oral functions and number of remaining teeth have statistically significant correlation with the mortality of older adults [ 10 ]. However, the number of remaining teeth was conflicting.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, oral functions, especially masticatory function, can be the predicator for mortality. A study has shown that oral function and serum levels albumin, which represent the nutritional status, affect mortality independently [ 10 ]. In this study, nutritional status had correlation with oral health behavior, which reflects health literacy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The three-parameter logistic model by item response theory (IRT) was used to identify items and calculate discriminations, difficulty, and guessing for each tooth type [ 34 , 35 , 36 , 37 , 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…We visited their homes at 10:00 in the morning to minimize the effect of food intake. Details of the survey were described in our previous report [27,28,37,38].…”
Section: Subject and Settingmentioning
confidence: 99%